Catalysis and temperature dependence on the formation of ZnO nanoparticles and of zinc acetate derivatives prepared by the sol-gel route - Tokumoto, M. S.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Briois, V (Amer Chemical Soc, 2003)
The chemical and structural nature of powders prepared from the zinc acetate-derived precursor using the sol-gel route is discussed. The influence of the synthesis temperature and of the hydrolytic catalyst on the structural features of the powder is focused on the basis of X-ray powder diffraction (XRPD) and extended X-ray absorption fine structure (EXAFS) measurements and complemented with density and thermoanalysis (TG-DTA) results. EXAFS and XRPD results show that no-washed nanoparticulate powders are composed of a mixture of ZnO (wurtzite), zinc acetate, and zinc hydroxyacetate. The latter has a layered structure typical of hydroxy double salts (HDS). The main component of no-washed powders is always unreacted zinc acetate solid but the relative amount of the zinc-based compounds depends on the nature of the hydrolytic catalyst, hydrolysis ratio, and of synthesis temperature. According to the proportion of the three zinc-based compounds, three families of powders could be distinguished. The amount of ZnO nanoparticles (1.6 +/- 0.6 nm) decreases as the synthesis temperature increases, as the hydrolysis ratio decreases, or by changing from basic to acid catalysis. This finding suggests that the formation of zinc compounds is controlled by the equilibrium between hydrolysis-condensation and complexation-reprecipitation reactions.